Toward an improved description of constraint release and contour length fluctuations in tube models for entangled polymer melts guided by atomistic simulations - Stephanou, Pavlos S.; Baig, Chunggi; Mavrantzas, Vlasis G. (My University, 2011)
By mapping atomistic trajectories accumulated in the course of long molecular dynamics simulations onto the tube model for model mono- and bidisperse polyethylene and cis-1,-4 and trans-1,4-polybutadiene melts, we have computed contributions to chain dynamics in entangled polymers from pure reptation, contour length fluctuation, and constraint release. We find that the tube diameter is the same in the matrices with molecular weight (MW) above the characteristic value Me for the formation of entanglements, but becomes larger in the matrices with MW below Me, in agreement with the Viovy et al. hypothesis. Additional results for the segment survival probability function ψ(s,t) have been used to propose modifications to the dual constraint model of Pattamaprom et al. and to the Leygue et al. model. © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: constraint release; contour length fluctuations; molecular dynamics simulations; primitive path analysis; tube model